Formulation and Physicochemical Properties of Meatless Floss - Mohd Jafri, Rusyada Aini; Abdullah, Norazlin (Enhanced Knowledge in Sciences and Technology, 2023)
Meat is a perishable food that susceptible to chemical deterioration and microbial growth, hence can be processed into other food products such as meat floss to increase the shelf life. Currently, meatless products are in high demand to prevent health problems due to excessive consumption of red meat and processed meat. Therefore, meatless floss made from young jackfruit and banana blossom was developed. Young jackfruit and banana blossom are ideal meat substitutes because it has a tender texture identical to shredded chicken and flaky texture, respectively. This study aimed to develop and characterize the different proportion of young jackfruit and banana blossom in meatless floss formulation. Simplex lattice design was used to adjust the proportion of young jackfruit and banana blossom. The sensory evaluation using affective test based on sensory properties had no significant difference (p > 0.05) between the floss samples as the panellists could not distinguish the difference. The physicochemical properties of the floss samples were analyzed including moisture content, ash content, protein content, texture and colour to determine the optimized meatless floss formulation. As the conclusion, the optimized meatless floss was 100% banana blossom based on the texture analysis of firmness with error below than 10%.